Study of some production techniques of ripened salami; preparation of traditional products ripened for long time, use of traditional and innovatory operations - Baldini P.; Diaferia C.; Spotti E.; Follini A.; Sarra G.; Berni E.; Palmisano S. (5. International Symposium on the Mediterranean Pig, 2007)
In almost all countries of Mediterranean Europe, different types of meat products are sold under the generic name of cured sausages: Starting from the first decades of 1900 these productions ceased to be homemade to become handicraft and industrial. With the aid of new scientific achievements, different techniques were then developed for some unit operations such as meat cooling and thermal conditioning; grinding of muscle and fat components; mixing with different ingredients and additives; filling in natural or artificial casings; ripening, carried out at temperatures close to room temperature and separation into some stages: heating, fermentation, drying and curing. It is common opinion that handicraft salami was less acid, less gummy and had a more pronounced aroma although it was often fatter. In order to prepare more traditional salami, some technologies were evaluated at SSICA which, as far as possible and consistent with safety requirements, followed the more traditional ones.
5. International Symposium on the Mediterranean Pig, 2004/09/16-19, Tarbes (France)